Research Status and Prospect of Fluorescence Detection of Antibiotics Based on Metal-Organic Frameworks (MOFs) - Yan, Deji (Transactions on Environment, Energy and Earth Sciences, 2026)
Antibiotic residues pose a serious threat to the ecological environment and human health. The development of rapid and sensitive detection methods is of great significance. This paper systematically reviews the research progress of fluorescence sensing platforms based on Metal-Organic Frameworks (MOFs) in antibiotic detection in recent years, with emphasis on their luminescence mechanisms and sensing principles, and analyzes the regulatory effects of ligand design, metal center selection and pore engineering on detection performance, and then proposes structure-performance optimization strategies to provide new ideas for the rational design of highly selective MOFs sensors. The typical applications of this type of material in the detection of tetracyclines, quinolones, sulfonamides, nitroimidazoles and nitrofurans are summarized, demonstrating its high sensitivity, excellent selectivity and fast response characteristics. And through efficient identification verification of trace antibiotics in complex matrices such as water and food, it provides a technical path for the MOFs sensing platform to transform from laboratory research to actual detection. This review particularly highlights the significant breakthroughs of MOFs in multimodal analysis, visualization and field detection, and looks forward to the current challenges and future development directions, providing a reference for the continuous innovation in this field.